RETRACTED: Study Motivation, Academic Performance and Career Commitment in Accounting Profession - Handoyo, Sofik (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This article has been retracted: please see Journal Policy on Article Withdrawal. This article has been retracted at the request of the Editor-in-Chief.The authors have plagiarized part of a paper that had already appeared in Journal of Education and Learning (EduLearn), Vol 12, No 3 10.11591/edulearn.v12i3.8078. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.